(untitled) (Comunicação & Inovação, 2020)
With the rapid dissemination of the new coronavirus (COVID-19) on a global scale, social distance became an important form of containing the pandemic and to prevent the depletion of the health system. In the face of this long worldwide quarantine, an unprecedented situation in human history, this study aims to discuss changes in emotional well-being and how social media has been used for relationship maintenance during the isolation period. Based on a quantitative survey (N = 725), this paper discusses how online interactions were conducted as a way of coping with social isolation.